The Effect of Emission Information on Housing Prices in Germany - Alexander Rohlf; Daniel Römer; Kathrine von Graevenitz (University of Heidelberg, Department of Economics, 2014)
In this paper, we study the effect of the release of emission information on housing prices. The main event under study is the release of the first wave of data from the European Pollutant Release and Transfer Register (E-PRTR) publishing emission quantities for the reporting year 2007. We base our analysis on quarterly house prices at the German postal code level for the years 2004-2011 and provide, to the best of our knowledge, the first analysis outside the US on this research question. We estimate a differences-in-differences model and find no significant effect of the release of emission information on the value of houses in affected postal code areas when controlling for observable differences in land use, prevalence of housing types, tax revenues and other postal code area characteristics by means of propensity score matching. This result survives several robustness checks. We conclude that disclosing the first wave of E-PRTR emissions had no robust impact on housing prices.
urn:nbn:de:bsz:16-heidok-162526
Keywords: 330